Transactional Leadership: Employee Performance and Organizational Performance (Literature Review) - Wenny Desti Febrian; Muliyati; Lily; Muhammad Rajab; Muhammad Thamrin AR (East Asian Journal of Multidisciplinary Research, 2023)
The purpose of this scientific article is to search for literature in support of the variables in this scientific article and given results for consideration in future research as research gaps or with different research objects. The research method used is qualitative with literature reviews to get results.  The results were obtained Most of the scientific articles of the review literature had a significant effect on the transactional leadership  variable with employee performance ,  as well as the employee  performance variable with organizational performance.